[Miklós Borz 2.]
1937-1940: interior of warehouses in the Vásártelep, police-dogs, car-race in Budapest, International Fair in Budapest, the slaughterhouse, skating rink, funeral ceremony in the Netherlands, 4 German newsreels (1939/2, 4,6, 1940/9), occupation of the Netherlands